Optimized coil and current flow designs for wireless charging containers with improved even magnetic flux density distribution - Liang, Rui (2024)
This paper introduces three different shapes of wireless charging containers (i.e. quadrangular prism, octagonal prism, and hexagonal prism) and presents optimal current flow designs for the coils to enhance the uniformity of magnetic flux distribution inside the containers. Additionally, the concept of folded coil design is introduced to further improve the even distribution of magnetic flux density within the containers. The performance of these designs is evaluated through simulations and practical experiments.